"Find that Balance:" The Impact of Cultural Consonance and Dissonance on Mental Health among Utah and Mormon Women. (20th June 2019) - Dengah, H. J. François; Bingham Thomas, Elizabeth; Hawvermale, Erica; Temple, Essa
Abstract: Cultural consonance and religious participation are both associated with salutogenic mental health outcomes. Yet studies of religious and other cultural models must take into account multiple and conflicting cultural norms. In this article, we explore the consequences of trying to adhere to the oppositional cultural models of religious (Latter‐day Saint or Mormon) and secular American gender roles as perceived by college‐aged women at a Utah university. Using cultural consensus and cultural consonance analysis, we demonstrate that while conforming with one model may provide social and mental health benefits, striving for consonance with both results in increased perceived stress levels for Latter‐day Saints and nonmembers alike. Such cultural dissonance may be a contributing factor to the current mental health crisis among Utah youth. This work expands the theory of cultural consonance by examining it in the context of two incongruent lifestyles.